The Contribution of Shaykh Muhammad Arsyad Al-Banjari in Spreading Islam in Nusantara - Dzulkifli Hadi Imawan (The Institute of Research and Service Community IPMAFA Pati, 2021)
This study will examine the contribution of Shaykh Muhammad Arsyad Al-Banjari in grounding Islam in the archipelago in the 18th century AD. He had a major contribution in grounding Islam in Nusantara in the 18th century AD. He left a great legacy in the form of scholarly works in various funun (Kitab Kuning) and also Pesantrens. Therefore, this study is to examine how far the contribution of Shaykh Muhammad Arsyad Al-Banjari in grounding Islam in Nusantara through the Kitab Kuning and his Pesantren in the 18th century AD. This study is qualitative with a historical approach and a research library. The results of this study state that Shaykh Muhammad Arsyad Al-Banjari contributed greatly in grounding Islam in Nusantara through the Kitab Kuning and also through the Pesantren Dalam Pagar which produces many national figures to date.